Hepatoprotective effect of Ecballium Elaterium fruit juice against paracetamol induced hepatotoxicity in male albino rats - Elmhdwi, Maraia Farag; Muftah, Saleh Mosbah; El tumi, Salem Gaber; Elslimani, Fatma Al-zaroug (International Current Pharmaceutical Journal, 2014)
This study was designed to investigate the antioxidant and hepatoprotective activity of Ecballium elaterium "Fruit juice" extract against paracetamol induced hepatotoxicity in male albino rats. The hepatotoxicity was induced by acetaminophen (PCM) at dose of 400 mg/kg in male albino rats. It was administered orally once a day, every 48 h at the same time for twenty two days. The biochemical liver functional tests ALT, AST, ALP, total bilirubin, total protein, antioxidant enzymes (GR, GPx, CAT, SOD), and histopathological changes were examined. Our results showed that Levels of liver enzymes ALT, AST, ALP, G-GT and total bilirubin and MDA level were significantly enhanced by administration of acetaminophen and level of total protein while antioxidant enzymes "GR, GPx, CAT, SOD" were decreased. However, the pretreatment with The E. elaterium "fruit juice" at 1 ml/kg orally revealed attenuation of serum ALT, AST, ALP. The histopathological studies also supported the protective properties of E. elaterium "fruit juice". The area of necrosis and degeneration of hepatocytes were observed in the toxic group. The prophylactic and curative groups showed a marked protective effect with decreased necrotic zones and hepatocellular degeneration. The present results clearly demonstrate the marked antihepatotoxic effects of E. elaterium "fruit juice" extract through its antioxidant activity on acetaminophen induced hepatotoxicity in rats. DOI: http://dx.doi.org/10.3329/icpj.v3i5.18535 International Current Pharmaceutical Journal, April 2014, 3(5): 270-274